2022
DOI: 10.1038/s41598-022-21102-w
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis and prediction of the metabolic state of stress-induced viable but non-culturable Bacillus subtilis cells

Abstract: Many bacteria adapt their physiology and enter the viable but non-culturable state to survive prolonged exposure to adverse environmental conditions. The VBNC cells maintain active metabolism, membrane integrity and gene transcription. However, they lose the ability to form colonies on a conventional culture media. Thus, standard colony counting methods cannot detect these alive but dormant cells. The Gram-positive bacterium Bacillus subtilis was found to enter the VBNC state when pre-exposed to osmotic stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…The physical changes seen in the outer membrane of VBNC F. tularensis LVS may also affect permeability for various antibiotics. It will also be interesting to test if antibiotic challenge can promote entry into the VBNC state, as has been observed for B. subtilis ( Morawska and Kuipers, 2022 ). Also, whilst we show that there is no change in optical density, fluorescence, or shape in the VBNC cells when challenged with gentamicin, we cannot exclude the possibility that these VBNC bacteria are, in fact being killed, but in contrast to culturable cells do not manifest any changes in morphology or optical density.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The physical changes seen in the outer membrane of VBNC F. tularensis LVS may also affect permeability for various antibiotics. It will also be interesting to test if antibiotic challenge can promote entry into the VBNC state, as has been observed for B. subtilis ( Morawska and Kuipers, 2022 ). Also, whilst we show that there is no change in optical density, fluorescence, or shape in the VBNC cells when challenged with gentamicin, we cannot exclude the possibility that these VBNC bacteria are, in fact being killed, but in contrast to culturable cells do not manifest any changes in morphology or optical density.…”
Section: Discussionmentioning
confidence: 95%
“…Transcriptomics was first applied as a tool to analyze VBNC populations of Vibrio cholerae ( Asakura et al, 2007 ), and is increasingly being used to investigate the molecular mechanisms involved in the transition into and maintenance of the VBNC state in bacteria ( Liu et al, 2016 ; Su et al, 2016 ; Zhong and Zhao, 2019 ; Morawska and Kuipers, 2022 ). We used two sequencing platforms, Oxford Nanopore and Illumina to analyze the transcriptional changes in F. tularensis LVS as it enters into the VBNC state ( Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…26,27 When bacteria encounter harsh environmental conditions, they can enter a VBNC state, which allows them to sustain basal metabolic rate by down-regulating the expression of genes involved in central metabolism. 17 Under BP nanosheet stress, a comprehensive analysis identified 72 pathways, with 69 showing up-regulation and 178 showing down-regulation of DEGs compared to the control group. Among these pathways, 51 were found to be related to metabolism, with 60 (which was not certified by peer review) is the author/funder.…”
Section: Metabolic Response To Bp Nanosheetsmentioning
confidence: 99%
“…20 Furthermore, the induction mechanisms of the VBNC state have been elucidated in various bacterial strains, including E. coli, Lactobacillus acetotolerans, and Rhodococcus biphenylivorans, with studies demonstrating that changes in gene expression in VBNC cells depend on the specific inducer. 17 Several studies have shown that nanomaterials can induce bacteria to enter the VBNC state. For example, silver nanoparticles have been identified as inducers of the VBNC state in Pseudomonas aeruginosa (P. aeruginosa).…”
Section: Introductionmentioning
confidence: 99%
“…33 Meanwhile, it has been proved that oxidative damage observed in B. subtilis leads to increased expression of katA (a catalase encoding gene) and namA (an antioxidant enzyme gene), which protect the cell from oxidative stress. Osmotic stress 42 and antibiotic treatment 24 have been previously reported to lead to transcriptional upregulation of these genes.…”
Section: Environmental Science: Nano Papermentioning
confidence: 99%